Efektivitas Program Posyandu Balita Di Desa Salumpaku Kecamatan Banawa Selatan Kabupaten Donggala - Nurhidayah; Tawil, Muzakir; Samsu, M. Kafrawi Al-kafiah; Ariyani, Risma (JPS: Journal of Publicness Studies, 2025)
This research aims to determine the effectiveness of the integrated toddler service post program in Salumpaku Village, South Banawa District, Donggala Regency. The theory used in this research is the theory from Richard M Steers in Duncan (1985:53)) which consists of 3 indicators. The data collection technique used is in-depth observation of informant interviews and documentation to collect the required data in the form of primary data and secondary data. Based on the research results obtained, it can be concluded that the effectiveness of the integrated postal service program for children under five in Salumpaku Village is not yet fully effective, in which the indicators of goal achievement, integrity and adaptation have not been effective because the goal has not been achieved. It cannot be said that the goal has been achieved in Salumpaku Village due to not being educated. well because the community of mothers of toddlers tends to still be ignorant and still affected by an unfavorable environment, the distance is also a barrier, and. Then, integrity can be said to be ineffective because the aim of the cadres is not being able to provide an understanding of the program, especially for toddlers aged 0-5 years, which is the golden age for children's growth which must be monitored optimally, as well as a lack of education regarding the importance of Posyandu for toddlers. Next, the adaptation indicator is not yet effective. This indicator is not yet fully effective due to the lack of quality cadres and lack of infrastructure for implementing posyandu.